Doing well by doing good in a globalized world: the moderating effect of internationalization on the relationship between corporate social responsibility and financial performance - Melcher, Maximilian Alexander (2019)
The study proposes internationalization as a novel perspective on the relationship between Corporate Social Performance (CSP) and Corporate Financial Performance (CFP), in another attempt to alleviate the inconclusiveness surrounding the existing results of the decade-spanning research on the CSP-CFP relationship. As the topic has not been addressed in a similar fashion so far, the study first establishes the foundation for the subsequent analyses by reviewing the existing literature on the CSPCFP relationship. The review unravels the various theories and empirical models, with which prior research has approached the topic, shedding light on the sources of the mixed research results. Several approaches contributing to overcoming the inconclusiveness are proposed, of which the effect of internationalization on the CSPCFP relationship is identified as a research gap worth pursuing in the study. To answer the question of how internationalization impacts the CSP-CFP relationship, a number of research hypotheses directed at uncovering and exploring the suspected effects of internationalization (INT) on the CSP-CFP relationship are formulated, drawing on additional literature reviews of the adjacent component relationships INTCSP and INT-CFP. Starting from a general perspective on the basic CSP-CFP relationship, which is taken to confirm the replicability of the prevalent research results with the compiled dataset, the hypotheses are gradually refined to incorporate the quantitative and qualitative dimensions of internationalization and eventually more sophisticated constructs aimed at uncovering factors augmenting the CSP-CFP relationship. The hypotheses are tested using a large sample of firms from 50 countries spanning 13 years. Qualitative as well as quantitative internationalization are found to be important factors impacting the relationship. When combined with CSP, quantitative internationalization was not found to moderate the CSP-CFP relationship, whereas the home-country governance quality as one important dimension of qualitative internationalization was found to positively moderate it. The combination of CSP, quantitative internationalization and the home-country governance quality in turn was not found to moderate the relationship. Limitations of the study as well as implications for the research on the topic are discussed, highlighting those parts that cannot be addressed with the currently accessible data and thereby opening them up to future research.